Development of fat digestion in infancy. Issue 3 (1st May 1999) - Manson, W G; Coward, W A; Harding, M; Weaver, L T
Abstract : AIM: To measure the development of fat digestion in early life, using a stable isotope breath test. METHODS: A combined longitudinal and cross sectional study was performed on 30 term and preterm infants using 13 C-labelled mixed triglyceride (MTG). Seventy six tests were performed in all. Results were expressed as cumulative percentage dose recovered over 6 hours (cPDR). RESULTS: Eighteen of 34 tests performed on infants under 30 days of age showed cPDRs below the normal range for adults and older children. The remainder of tests, performed on infants over 57 days of age, all showed cPDRs within the normal range. Peak PDR correlated significantly (r = 0.928, p<0.01) with cPDR. CONCLUSION: The capacity to digest fat is incomplete at birth, but quickly develops to normal levels during the first months of life. The MTG breath test is a useful non-invasive method to measure the development of fat digestion in early life.